The Izon of the Niger Delta (Book collections on Project MUSE., 2014)
The Izon of the Niger Delta is a global history of the Izon, Ijo or Ijaw people from their homelands in the Niger Delta, through Nigeria, the West and Central African coastlands, and in the African diaspora into Europe, the America and the Caribbean. It is a preliminary study that raise questions and opens ground for further research. The book provides chapters that take an overview of issues on the environment of the Niger Delta, an analysis of the Ijo population, the language, culture, resources, history and linkage to the rest of Nigeria and the world. In effect these chapters provide a syn.